2006
DOI: 10.1631/jzus.2006.b0690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected fungi on the reduction of gossypol levels and nutritional value during solid substrate fermentation of cottonseed meal

Abstract: Abstract:The objective of this work was to investigate the effect of six individual strains of fungi on the reduction of gossypol levels and nutritional value during solid substrate fermentation of cottonseed meal (CSM). Six groups of disinfected CSM substrate were incubated for 48 h after inoculation with either of the fungi C. capsuligena ZD-1, C. tropicalis ZD-3, S. cerevisae ZD-5, A. terricola ZD-6, A. oryzae ZD-7, or A. niger ZD-8. One not inoculated group (substrate) was used as a control. Levels of init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 10 publications
2
38
0
Order By: Relevance
“…O-phosphoserine is a product of carbon metabolism, and it is a precursor substance that forms many amino acids, such as glycine, serine, threonine, cysteine, and methionine. The significant elevation of O-phosphoserine in the treatment groups showed that broilers fed the control diet needed to generate more amino acid by endogenous metabolism; that was different from the FCSM diet, which included lots of amino acid via microbial fermentation (Zhang et al, 2006;Tang et al, 2012). This was further supported by the decrease of 3-hydroxypyruvate and increase of glutamine or glycine.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…O-phosphoserine is a product of carbon metabolism, and it is a precursor substance that forms many amino acids, such as glycine, serine, threonine, cysteine, and methionine. The significant elevation of O-phosphoserine in the treatment groups showed that broilers fed the control diet needed to generate more amino acid by endogenous metabolism; that was different from the FCSM diet, which included lots of amino acid via microbial fermentation (Zhang et al, 2006;Tang et al, 2012). This was further supported by the decrease of 3-hydroxypyruvate and increase of glutamine or glycine.…”
Section: Discussionmentioning
confidence: 92%
“…The utilization of CSM is limited in poultry diets due to the presence of gossypol, a toxic polyphenol. However, to solve this problem, solid-state fermentation is an effective option (Zhang et al, 2006;. Additionally, CSM by solid-state fermentation improves nutrition characteristics (Zhang et al, 2006;Sun et al, 2012;Yang et al, 2012) and produces many essential nutrients such as amino acids, small-size peptides, vitamins, and oligosaccharides .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, CSM fermented with C. tropicalis and Aspergillus niger could increase the crude protein content and in vitro digestibility as well as markedly decrease the FG content (12,13). Additionally, fermentation of : Means within a row that have different superscript letters are significantly different (P < 0.05).…”
Section: Growth Performance and Digestibilitymentioning
confidence: 99%
“…CSM was fermented by Candida tropicalis and C. tropicalis plus Saccharomyces cerevisiae. These strains could detoxify FG and improve the nutritional value in CSM in our previous study, and the strain C. tropicalis was more effective at detoxifying FG in CSM than S. cerevisiae (12,13). Considering the reduction of FG level, CSM was not treated with only S. cerevisiae.…”
Section: Introductionmentioning
confidence: 97%